2016
DOI: 10.1177/1098612x16643124
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and response in cats with neoplasia treated with toceranib phosphate

Abstract: Objectives Toceranib phosphate is a tyrosine kinase inhibitor licensed for the treatment of non-resectable Patnaik grade II/III recurrent cutaneous mast cell tumours in dogs. There is no information in cats regarding the tolerated dose, toxicity or tumour response of this drug. The aim of this study was to analyse retrospectively a cohort of cats with advanced neoplasia treated with toceranib to identify toxicity and response. Methods The medical records of the Small Animal Teaching Hospital were reviewed. Cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 15 publications
0
28
0
1
Order By: Relevance
“…The most commonly reported side effect of toceranib in cats is anorexia, with diarrhoea and vomiting seen in 25%–30% of cats; however, two reports noted severe hepatotoxicity associated with serum alkaline phosphatase or alanine transaminase elevations in 6 of 32 cats . Another study showed although 60% of cats had some side effects, nearly 90% were low grade and resolved without direct intervention .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly reported side effect of toceranib in cats is anorexia, with diarrhoea and vomiting seen in 25%–30% of cats; however, two reports noted severe hepatotoxicity associated with serum alkaline phosphatase or alanine transaminase elevations in 6 of 32 cats . Another study showed although 60% of cats had some side effects, nearly 90% were low grade and resolved without direct intervention .…”
Section: Discussionmentioning
confidence: 99%
“…Toceranib (Palladia; Zoetis) is licensed for the treatment of cutaneous mast cell tumours in dogs. Off‐label usage in cats has been described for a variety of tumour types including oral squamous cell carcinoma, injection site sarcoma, mast cell neoplasia and pancreatic carcinoma . In cats, the most common toxicities of toceranib include mild gastrointestinal signs and myelosuppression which are self‐limiting or resolve with a dose adjustment or treatment break.…”
mentioning
confidence: 99%
“…In addition, combining chemotherapy with RT for humans with high-risk salivary gland carcinomas (ie, those with large and invasive primary tumours, close or incomplete margins, high histopathological grade, histological evidence of neural or vascular invasion, or positive lymph nodes) does not offer survival benefit but does increase morbidity, so is not recommended. 31 Toceranib phosphate has been used in cats with a variety of malignancies, including carcinomas and adenocarcinomas, and is generally well tolerated, [32][33][34] but data on response are limited. The short median durations of treatment (40, 77 and 100 days, respectively) [32][33][34] in the toxicity studies suggest that there is often relatively rapid disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Toceranib and masitinib have been approved for veterinary use in dogs, particularly for mast cell tumours . However, a range of anti‐angiogenic drugs, either alone or in combination, has been used to treat a wide variety of canine and feline neoplasms, including osteosarcomas, melanomas, fibrosarcomas, histiocytic sarcomas, haemangiosarcomas, lymphomas and prostatic, thyroid, nasal, gastric, mammary, pulmonary, biliary, salivary, anal sac and urinary bladder carcinomas …”
Section: Control Of Angiogenesismentioning
confidence: 99%
“…In the majority of these veterinary studies, tocerinab was used, sometimes alone [29][30][31][32][33][34][35][36][37] or, more commonly, in combination with other drugs such as cyclophosphamide (belonging to the nitrogen mustard group of alkylating agents), 38,39 vinblastine (an antimitotic alkaloid), 40,41 carboplatin (a platinum-containing complex), 42,43 lomustine (1-(2-chloroethyl)-3-cyclohexyl-1-nitrosurea (or CCNU), which belongs to the nitrosurea group of alkylating agents), [44][45][46] doxorubicin (an anthracycline antibiotic) [47][48][49] and piroxicam (a nonsteroidal anti-inflammatory drug (NSAID) with cyclooxygenase (COX)-2 inhibiting properties). 38,[50][51][52] Masitinib has also been evaluated in dogs.…”
Section: Control Of Angiogenesismentioning
confidence: 99%